THE PERCEIVED IMPACT OF TPR METHOD ON EFFECTIVENESS OF STUDENTS’ ENGLISH VOCABULARY IN SDN KALIBANGER - Dwiki Mifta Saputra; Sahid Sahid (CLLiENT (Culture, Literature, Linguistics, and English Teaching), 2023)
Enhancing the English vocabulary for the students become one of the most important part to have a good ability in English (speaking, listening, reading and also grammar). The perception of students toward the running process of increasing the English vocabulary are important to know. This study aims to investigate the students’ perception of using TPR (Total Physical Response) method on the effectiveness of studying English vocabulary and to what extend does TPR (Total Physical Response) method improve students’ English vocabulary. The quantitative data is obtained by conducting the Pre-Test and Post-Test Activity 1 and Post-Test Activity 2. And qualitative is to support the quantitative data. The result that that the Total Physical Response (TPR) method is very effective to help the students of enhancing the English Vocabulary. The students perceive that using Total Physical Response (TPR) method is more effective than using the conventional method. They feel that use the TPR method is more fun and exciting. They can feel the progress of mastering the English vocabulary. Then the quantitative data shows that the result in Post-Test Activity 1 in Controlled Class shows that there is an increase from the Pre-Test. In Pre-Test, the average is 61,7 that belongs to Enough category, then in Post-Test Activity 1, the average is 66,1 (Enough Category). Then in a Post-Test Activity 2, the average result is 67,8 (Enough category). We can conclude that in Controlled Class that uses the conventional method still has a progression toward the vocabulary achievement but it is really hard or not significant. The result in Post-Test Activity 1 in Experimental Class shows that there is an increase from the Pre-Test, it is from 66,9 (Pre-Test) to 74,4 (Post-Test Activity 1). It is a proofed that there is increase of 7.5 point (from Pre-Test to Post-Test Activity 1), it is more effective than we use the conventional method that only increase 4.4 point. It happens also in the Post-Test Activity 2 in Experimental Class, there is an increase 6.2 point (from Post-Test Activity 1 to Post-Test Activity 2). It is more effective than we use conventional method that only increases 1.7 point (from Post-Test Activity 1 to Post-Test Activity 2).